Makna Kata δικαιοσυνη dalam Matius 5:17-48 dan Implikasinya Bagi Kehidupan Orang Percaya Masa Kini - Harrye, Windy Denise Anastsya (Institut Agama Kristen Negeri Palangka Raya, 2022)
People who believe have standards in living their lives in the world and the fact is that there are not a few people who believe today who no longer make the word of God the standard, but themselves. Obedience in carrying out the law is a truth that must be upheld and at the same time they stumble with the measurement they are using because it is not in accordance with the word of God. In the study of the Gospel of Matthew 5: 17-48 the author uses qualitative methods and uses the hermeneutic principle method which refers to the principles and ways of exegesis and exegesis in which interpretation focuses on a passage of the Bible and systematically and thoroughly finds its original meaning. The author also uses the exposition by paying attention to the application and relationship of the passage in the Bible to the circumstances under study by the author. The results of the study found that the phrase